2022
DOI: 10.30738/union.v10i2.12476
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students' Mathematical Problem-Solving Ability on Trigonometry

Abstract: This investigation aims to examine problem-solving ability (PSA) in Polya's problem-solving phases in the material of sine and cosine number and difference. This study used the descriptive qualitative research method. This study looked at 33 students in Class XI MIPA 5 from SMA Negeri 2 Bantul. Data was collected using written tests and interviews. The written test in this study takes the form of a two-point description question. The study's findings were used to calculate the mathematics PSA of students in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Research on the ability of students to measure triangles using a degree arc yielded variable results. Hardison (2020) and Perkasa (2022) both found that students had difficulties in measuring angles, with…”
Section: Introductionmentioning
confidence: 99%
“…Research on the ability of students to measure triangles using a degree arc yielded variable results. Hardison (2020) and Perkasa (2022) both found that students had difficulties in measuring angles, with…”
Section: Introductionmentioning
confidence: 99%